Application of additional dose of N could sustain rice yield and maintain plant nitrogen under elevated ozone (O3) and carbon dioxide (CO2) condition - Chakrabarti, Bidisha; Sharma, Sheetal; Mishra, Ajay Kumar; Kannojiya, Sudha; Kumar, V.; Bandyopadhyay, S. K.; Bhatia, Arti (Frontiers in Sustainable Food Systems, 2024)
Introduction Global food security is challenged by the increasing levels of air pollutants like ozone (O3) through their impacts on crop productivity. The present study was conducted to quantify the interactive effect of elevated ozone (O3) and carbon dioxide (CO2), on different rice varieties in northern India. Methods An experiment was conducted in Genetic H field, Environment science, IARI for two consecutive years (2020 and 2021) during the kharif season, to quantify the impact of elevated O3 and CO2 interaction on productivity, and plant N in three rice varieties (Pusa basmati 1121, Nagina 22, IR64 Drt1) under different nitrogen (N) management practices. Rice crop was grown in Free Air Ozone-Carbon dioxide Enrichment rings (FAOCE) rings with two levels of O3 (elevated 60 ±10ppb and ambient) and two levels of CO2 (elevated, 550±25 ppm and ambient) concentration and their interaction with two N fertilizer treatments i.e., 100% RDN (recommended dose of N) and 125% RDN. Results and discussion Elevated O3 significantly decreased physiological parameters like photosynthesis rate, stomatal conductance and transpiration rate of the crop. Grain yield reduced by 7.2-7.5%, in Pusa Basmati 1121 and from 6.9-9% in IR64 Drt1 varieties in elevated O3 treatment as compared to ambient treatment. Yield reduction in Nagina 22 variety was not significant in elevated O3 treatment. Elevated CO2 concentration of 550 ppm was able to fully compensate the yield loss in Nagina 22 variety and partially compensate (3.9-8.0%) in Pusa Basmati 1121 and IR64 Drt1 varieties. Grain N concentration in rice varieties decreased by 10.8-14.7% during first year and by 7.8-20.6% during second year in elevated O3 plus CO2 interaction treatment than ambient. Grain N uptake also decreased (13.2-17.1% in first year and 4.5-22.8% in second year) in elevated O3 plus CO2 interaction treatment as compared to ambient. Application of additional 25% of recommended dose of N improved grain N concentration, grain N uptake as well as available N of soil as compared to 100% RDN treatment in elevated O3 plus CO2 interaction treatment. Additional 25% N dose could help in sustaining rice productivity and quality under elevated O3 and CO2 condition.